Prediksi Pergerakan Saham Menggunakan William Fraktal dan Moving Average : Studi Pada Saham Sektor Industri Pertambangan di Bursa Efek Indonesia - Risaldi, Muh; Haanurat, A Ifayani; Jaya, Asri (Jurnal Riset Ilmu Ekonomi, 2024)
The deceleration of the global economy resulted in a significant decline in world commodity prices, especially coal. The decline in these commodities made the stock price of the coal subsector decline. This study aims to analyze the accuracy of William's moving average and fractal indicator prediction signals with actual results on stock charts. The method used in this study is the Mann Whitney test. The study's conclusions show that the use of both technical analysis indicators to predict the direction of changes or movements in stock prices produces accurate findings, with predictive signals from fractal indicators and moving averages not much different from each other. Based on the accuracy rates of 87% and 85% respectively for William's fractals and moving averages, it can be concluded that William's fractal indicator is significantly more reliable than moving averages in predicting buy and sell signals for mining stock. Based on the findings of this study, both short- and long-term investors can benefit from using the Williams fractal indicator to predict future price trends and identify when to buy and sell stocks to maximize profits.